2018
DOI: 10.5198/jtlu.2018.1059
|View full text |Cite
|
Sign up to set email alerts
|

How much is enough? Assessing the influence of neighborhood walkability on undertaking 10-minute walks

Abstract: Abstract:Neighborhood walkability is increasingly perceived as an effective way to support individuals' health, since living in a walkable environment is associated with increases in utilitarian walking. Yet, while people are more likely to walk in more walkable neighborhoods, increased walkability can also lead to walking shorter distances, thus mitigating the positive health outcomes associated with walkable environments. Given that the World Health Organization recommends physical activity to be performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…In other words, more people can walk and bike in areas with a higher density of public transportation. Third, other individual variables were correlated with active commuting, which is consistent with the results of previous empirical studies [39,80]. Individual factors such as age, gender, income, and car ownership were strongly correlated with active commuting.…”
Section: Discussionsupporting
confidence: 90%
“…In other words, more people can walk and bike in areas with a higher density of public transportation. Third, other individual variables were correlated with active commuting, which is consistent with the results of previous empirical studies [39,80]. Individual factors such as age, gender, income, and car ownership were strongly correlated with active commuting.…”
Section: Discussionsupporting
confidence: 90%
“…The time spent walking mostly comprised between 10 to 20 min (44%) and between 20 to 30 min (28%). These travel times were quite long considering the nature of utilitarian walking trips: they are much longer than the referential 10 and 15 min reported in some travel studies [14,18,37,82] and longer than the walking trips reported in other Southern European countries. For instance, in the Spanish city of Granada, Ferrer and Ruiz [30] described that 80% of walking trips are shorter than 20 min.…”
Section: Discussionmentioning
confidence: 65%
“…The Walkability Score is adapted from the Walk Score, which is an index that combines various variables that represent urban form such as density, diversity, and destination accessibility [21,62]. Since the Walk Score itself is a composite index of neighborhood walkability, there are some studies that include only itself as a neighborhood environmental variable [7,63]. However, one study found that there are some urban form elements such as land use diversity and walking route supply that the Walk Score does not include [21].…”
Section: • Neighborhood Environmental Variablesmentioning
confidence: 99%